CIVIC EDUCATION AT MUHAMMADIYAH HIGHER EDUCATION: DEVELOPMENT STUDY OF HAND BOOK OF MENUJU KEHIDUPAN YANG DEMOKRATIS DAN BERKEADABAN - Suidat Suidat; Adian Husaini; Didin Saefuddin; Endin Mujahidin (Universitas Muhammadiyah Surakarta, 2017)
Civic education is one of the basic courses that must be taken by every student at the College. The regulation of the course is based on the mandate contained in the law on the National Education System. Through Civic Education courses, the students can be directed national personality, that is how they love their homeland Indonesia, being a democratic, civilized, tolerant and so on. Muhammadiyah through the Council of Higher Education, Research and Development of Muhammadiyah head quarter published a textbook on Civic Education with the title Civic Education toward a Democratic and Civilized Life. The book became a staple in reference Civic Education Course in Universities of Muhammadiyah (PTM). However when elaborate on the Indonesian ideology or, in the book does not contain the formulation history of state basic ideology which was done by the founding fathers. Also how the role and Islamic thought figures who participated in formulating the state basic ideology be part of the material that was duly presented in the book. It is important that students who study in PTM to know and understand the history and struggle of Islamic figures in formulating the basis of the state and the dynamics that occurred at that time. So that their knowledge is complete and in understanding the Pancasila as the state basic ideology of Indonesia. Ki Bagus had very important role in the Committee for Indonesian Independence (PPKI) experienced of dead lock about the change of first principle of Pancasila, and there was serious debate and dynamic. Likewise, the role and thought of Kasman Singodimedjo was also important on the basis state in both the trial PPKI, as well as in the Constituent Assembly. Perpsektif Kasman about Pancasila based on Islam became important after the implementation of 1945 Constitution and Presidential Decree July 5th 1959. The role of Abdul Kahar Mudzakkir as a witness to the history of the struggle of Muslims cannot be neglected; especially Mudzakkir included in the Committee of Nine which develops the basic state eventually became the Jakarta Charter and accepted unanimously by BPUPKI. Furthermore, in the Constituent Assembly Mudzakkir remain committed to make Islam as the basis of the state, where the Constituent Assembly is the foundation of the momentum of the second volume formulation. The core of the Civics book is how the problem of state ideology especially Pancasila can be described in a comprehensive, complete and not partial. Including the relationship between the Jakarta Charter and the Constitution 1945. Other matters concerning aspects of citizenship is derived and the meaning of ideology or basic state. Therefore, this paper presents the role and thought of Ki Bagus Hadikusumo, Kasman Singodimedjo, and Abdul Kahar Mudzakkir become material development of Civic Education in the book of Civic Education toward a Democratic and Civilized Life.Pendidikan Kewarganegaraan merupakan salah satu mata kuliah dasar yang mesti ditempuh oleh setiap mahasiswa dalam studinya di Perguruan Tinggi. Ketentuan adanya mata kuliah ini berdasarkan amanat yang tertuang dalam undang-undang tentang Sistem Pendidikan Nasional. Melalui mata kuliah Pendidikan Kewarganegaraan ini mahasiswa diarahkan dapat berkepribadian nasional, yaitu bagaimana mereka cinta tanah air Indonesia, bersikap demokratis, beradab, toleran dan lain sebagainya. Muhammadiyah melalui Majelis Pendidikan Tinggi, Penelitian dan Pengembangan (Diktilitbang) Pimpinan Pusat Muhammadiyah (PP Muhammadiyah) menerbitkan satu buku teks tentang Pendidikan Kewarganegaraan (Civic Education) dengan judul Pendidikan Kewarganegaraan Menuju Kehidupan yang Demokratis dan Berkeadaban. Buku ini menjadi referensi pokok dalam Mata Kuliah Pendidikan Kewarganegaraan di Perguruan Tinggi Muhammadiyah (PTM). Akan tetapi ketika menguraikan tentang ideologi atau dasar negara Indonesia pada bagian yang membahas tentang “Membangun Identitas Nasional”, tidak memuat bagaimana sejarah perumusan dasar negara yang dilakukan para founding fathers. Bagaimana pemikiran tokoh-tokoh Islam seperti Ki Bagus Hadikusumo, Kasman Singodimedjo, dan Abdul Kahar Mudzakkir tidak menjadi bagian dalam materi yang sepatutnya disajikan dalam buku tersebut. Hal ini penting agar mahasiswa mengetahui dan memahami sejarah dan perjuangan tokoh-tokoh Islam dalam merumuskan dasar negara serta dinamika yang terjadi saat itu. Sehingga pengetahuan mereka menjadi utuh dan tidak parsial dalam memahami Pancasila sebagai dasar negara Indonesia. Peran Ki Bagus sangat penting ketika Panitia Persiapan Kemerdekaan Indonesia (PPKI) mengalami deadlock soal perubahan sila pertama dasar negara Indonesia. Demikian juga pemikiran Kasman Singodimedjo tentang dasar negara baik dalam sidang PPKI, maupun dalam sidang Konstituante. Perpsektif Kasman tentang Pancasila yang berbasis pada Islam menjadi penting setelah diberlakukan kembali UUD 1945 dengan lahirnya Dekrit Presiden 5 Juli 1959. Demikian juga pemikiran Abdul Kahar Mudzakkir sebagai saksi sejarah perjuangan umat Islam tidak bisa dilupakan begitu saja, Abdul Kahar Mudzakkir termasuk dalam Panitia Sembilan yang bertugas menyusun dasar negara yang pada akhirnya menjadi Piagam Jakarta. Dalam Sidang Konstituante Mudzakkir tetap komitmen menjadikan Islam sebagai dasar negara, di mana Sidang Konstituante adalah momentum perumusan dasar negara jilid kedua. Inti dari buku PKn adalah bagaimana masalah ideologi negara khususnya Pancasila dapat dijelaskan secara komprehensif, utuh dan tidak parsial. Termasuk hubungan antara Piagam Jakarta dan UUD 1945. Oleh karena itu disertasi ini membahas pemikiran Ki Bagus Hadikusumo, Kasman Singodimedjo, dan Abdul Kahar Mudzakkir menjadi bahan pengembangan materi Pendidikan Kewarganegaraan dalam buku ajar Pendidikan Kewarganegaraan Menuju Kehidupan yang Demokratis dan Berkeadaban.